Tradisi Ilmiah dan Pendidikan Islam: Integrasi Ilmu Pengetahuan dengan Nilai-Nilai Spiritual - Armedi, Rama; Sodikin, Satria; Kawakip, A Nurul (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2024)
Islamic education is the fundamental basis in making the character and identity of Muslims to always flourish open alongside the development of the times. The complexity of the challenges of Islamic education in the issues of modern society, in order to remain relevant and effective then need adaptation and innovation. The aim of this article is to know and understand Islamic education by integrating science with the values of spirituality as a strategic step in building a generation of Muslims in accordance with the demands of the times. Through a literature review approach, the study analyzes literature related to how to identify gap research and objects to be tackled in the implementation of Islamic education. The results of the research indicate that the concept of Islamic education developed by Syed Muhammad Naquib al-Attas is still relevant to Islamic Education today, namely by developing the potential of the students to be believing and fearful of the One God, being noble, healthy, knowledgeable, competent, creative, independent, and becoming a democratic and responsible citizen. This concept is also in line with the national educational objectives.